Investigation of Protein Binding With All Solid‐State Ion‐Selective Electrodes. Issue 8 (23rd July 2013) - Prabhu, Alok; Bobacka, Johan; Ivaska, Ari; Levon, Kalle
Abstract A potentiometric sensor for studying charge based adsorption of proteins was created using a single‐piece polyaniline‐PVC ion‐selective electrode (ISE). Three different ISEs, two for Na+ and one for Cl− ion determination, were studied. The Na+‐ISEs consisted of a neutral calixarene‐based ionophore and one with a charged carrier dinonylnapthalenesulfonic acid (DNNSA) whereas for the Cl− ISE, an anion exchanger tridodecylmethylammonium chloride (TDDMA+Cl−), was used. The Na+ ISE with DNNSA as the charged carrier was successfully able to discriminate the binding of two different proteins (bovine serum albumin and lysozyme) based on their intrinsic charge.